The handbook of art and design librarianship - Glassman, Paul; Dyki, Judy (Neal-Schuman, an imprint of the American Library Association, 2017)
The handbook examines methods of innovative librarianship in academic and art school libraries. Serving as a field guide to academic art libraries in the twenty-first century, it integrates theory and practice as demonstrated by creative professionals working in the field of art librarianship. While much attention has been paid to art librarianship as it exists in museum settings, the focus on academic art and design school information services has not been as intensive. This essential handbook addresses that gap in the professional literature and examines methods of innovative librarianship in academic and art school libraries. The book offers guidelines for information professionals working in art and design environments who support and anticipate the information needs of artists, designers, architects, and the historians who study those disciplines.